2004
DOI: 10.1152/ajpcell.00106.2003
|View full text |Cite
|
Sign up to set email alerts
|

FKBP12.6 and cADPR regulation of Ca2+ release in smooth muscle cells

Abstract: . FKBP12.6 and cADPR regulation of Ca 2ϩ release in smooth muscle cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(95 citation statements)
references
References 71 publications
5
90
0
Order By: Relevance
“…1A, 1B, 2A, and 2B). The inhibitory effect of CaN in C 2 C 12 cells is thought to depend on CaN, RyR, and the 12-kDa FK-506-binding protein (FKBP 12) being associated in a trimeric complex (37); however, within ASMCs, FKBP 12 does not bind to RyRs (44), providing support that CaN regulates ASMC RyR activity through a novel regulatory mechanism. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1A, 1B, 2A, and 2B). The inhibitory effect of CaN in C 2 C 12 cells is thought to depend on CaN, RyR, and the 12-kDa FK-506-binding protein (FKBP 12) being associated in a trimeric complex (37); however, within ASMCs, FKBP 12 does not bind to RyRs (44), providing support that CaN regulates ASMC RyR activity through a novel regulatory mechanism. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle contraction in isolated tracheal rings was measured using the organ bath technique, as described previously (44), with isometric transducers (Harvard Apparatus, South Natick, MA) and a PowerLab/4SP recording system (AD Instruments, Colorado Springs, CO). Tracheas were quickly removed from mice and transferred into ice-cold 1.8 mM PSS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, Wang and colleagues have provided evidence relevant to the mechanisms by which calcium release through RyR channels is brought forth in airway myocytes (23). The open state of the RyR channels in cardiac muscle cells is regulated by FK506-binding proteins (33).…”
Section: Cyclic Adp-ribose As An Endogenous Ligand For the Ryanodine mentioning
confidence: 99%
“…The open state of the RyR channels in cardiac muscle cells is regulated by FK506-binding proteins (33). Specifically, FKBP12.6 is known to associate with the RyR2 isoform in smooth muscle cells to regulate its function (23,34). In ASM cells, Wang and coworkers showed that, although both FKBP12 and FKBP12.6 mRNAs are expressed, the FKBP12.6 fusion proteins only associate with the RyR2 (23).…”
Section: Cyclic Adp-ribose As An Endogenous Ligand For the Ryanodine mentioning
confidence: 99%